2018
DOI: 10.3389/fphar.2018.00736
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Curcumae Longae Radix, Curcuma phaeocaulis Radix and Their Processed Products on Epo/EpoR Pathway and CD62p

Abstract: Background: Curcumae Radix (Yujin) has been widely used to treat Qi stagnation due to Liver depression (LDQS) in traditional Chinese medicine (TCM) for a long time and is good at dispelling melancholy by soothing liver to regulate qi and relieving pain by promoting blood circulation for removing blood stasis. Yujin stir-frying with vinegar can strengthen the effect of dispersing stagnated hepatoqi to stop pain by injecting medicine into the liver and stir-frying with wine can strengthen the effect of promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…54 As a herb used for blood circulation promotion in TCM, several studies have provided evidence that Curcumae Radix could improve the hemorheological state in animal models. 55,56 Intragastric administration of Curcuma longa root decoction (0.9 g•kg -1 , 2 weeks) was found to significantly reduce the serum levels of Epo, EpoR, and CD62p, thus reducing the formation of physiological thrombosis in experimental rats. 55 Moreover, Chen et al reported that the same extract of Curcumae Radix could significantly improve the abnormality of 5-HT in plasma, β-EP in brain, and inhibit the expression of c-fos, which led to an analgesic effect in rats.…”
Section: Antioxidant Activitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…54 As a herb used for blood circulation promotion in TCM, several studies have provided evidence that Curcumae Radix could improve the hemorheological state in animal models. 55,56 Intragastric administration of Curcuma longa root decoction (0.9 g•kg -1 , 2 weeks) was found to significantly reduce the serum levels of Epo, EpoR, and CD62p, thus reducing the formation of physiological thrombosis in experimental rats. 55 Moreover, Chen et al reported that the same extract of Curcumae Radix could significantly improve the abnormality of 5-HT in plasma, β-EP in brain, and inhibit the expression of c-fos, which led to an analgesic effect in rats.…”
Section: Antioxidant Activitiesmentioning
confidence: 97%
“…55,56 Intragastric administration of Curcuma longa root decoction (0.9 g•kg -1 , 2 weeks) was found to significantly reduce the serum levels of Epo, EpoR, and CD62p, thus reducing the formation of physiological thrombosis in experimental rats. 55 Moreover, Chen et al reported that the same extract of Curcumae Radix could significantly improve the abnormality of 5-HT in plasma, β-EP in brain, and inhibit the expression of c-fos, which led to an analgesic effect in rats. 57 Besides the anti-inflammation effect described above, curcumolide derived from Curcuma wenyujin was also reported to have an anti-angiogenic effect in HUVECs and in a murine oxygen induced retinopathy model of ischemia-induced retinal neovascularization.…”
Section: Antioxidant Activitiesmentioning
confidence: 97%
“…As recorded in Chinese Pharmacopoeia (2020 edition), the root tuber of Curcuma longa L. (RCL) can promote blood circulation and relieve pain, promote qi and relieve depression, clear heart and cool blood, and treat hepatitis with jaundice [ 3 ]. Modern pharmacological research has shown that it has a variety of biological activities including improving the blood stasis model [ 4 , 5 ], alleviating pain [ 6 ], anti-tumor activities [ 7 ], et al The rhizome of Curcuma longa L. (RHCL) is known as Jianghuang in Chinese. Its actions include promoting qi, breaking blood, unblocking the meridian, and relieving pain [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the metal oxide NCs, Bi 2 O 3 with a high atomic number has been reported to have the stopping power for high energy photons by being applied to the conversion layer [ 23 , 24 ]. Commonly used NCs are composed of hazardous substances with environmental problems, such as cadmium (Cd) and lead (Pb) [ 25 , 26 ]. Therefore, research on Cd- and Pb-free NCs has become more important, and use of In-based NCs, such as copper indium sulfide (CuInS 2 ) [ 27 ], indium phosphide (InP) [ 28 ], and indium zinc phosphide (InZnP) [ 29 ] tends to increase in photodetector, because they are quite similar to the Cd-based NCs in terms of optical properties and colloidal stability [ 30 ].…”
Section: Introductionmentioning
confidence: 99%